2010
DOI: 10.1016/j.trstmh.2009.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the healthcare burden of osteomyelitis in Uganda

Abstract: Chronic osteomyelitis is a considerable healthcare burden in many developing countries, but this burden is poorly quantified. To estimate the clinical burden of osteomyelitis we systematically sampled the medical records of orthopaedic clinics at five hospitals in Uganda. To estimate the surgical burden of osteomyelitis we reviewed the diagnosis in 9354 operations conducted during a 1 year period at the same five hospitals. Of 1844 outpatients with a documented diagnosis sampled over 1 year, 187 (10%) had oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 7 publications
1
47
2
Order By: Relevance
“…[3][4][5][6][7] The health care burden of chronic osteomyelitis in developing countries is reported to be essential. [8][9][10] Thus, for example in Uganda, 35% of all surgical procedures have been performed due to the diagnosis of osteomyelitis in 2010. One-third of these patients were children aged between 10 and 14 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7] The health care burden of chronic osteomyelitis in developing countries is reported to be essential. [8][9][10] Thus, for example in Uganda, 35% of all surgical procedures have been performed due to the diagnosis of osteomyelitis in 2010. One-third of these patients were children aged between 10 and 14 years.…”
Section: Resultsmentioning
confidence: 99%
“…One-third of these patients were children aged between 10 and 14 years. [9] The causal relationship is considered to be the often insufficient medical care, especially in the rural areas. Thus, minor injuries or open fractures may lead to a chronic osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 A study investigating the healthcare burden in Uganda reported that 3.5% of surgical procedures were for osteomyelitis, and 60% of these procedures were a sequestrectomy. 10 A retrospective study from a specialist orthopaedic hospital in Malawi reported that 6.7% of all orthopaedic procedures in children were for chronic osteomyelitis, the majority being a sequestrectomy. 11 Approximately 16% of children required a reconstructive procedure.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…10 already scarce resources [58]. In these parts of the world simplified treatment schemes adapted to take into consideration local circumstances are needed.…”
Section: Referencesmentioning
confidence: 99%